Series de tiempo en panel: Una rese\~na de la evolución metodológica - Tamara Burdisso; Máximo Sangiácomo (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2015)
– The document focuses on the econometric treatment of macro panels, known in literature as panel time series. This new approach rejects the assumption of slopes' homogeneity and handles nonstationarity. It also recognizes that the presence of cross-section dependence (CSD), i.e. some correlation structure in the error term between units due to the presence of unobservable common factors, squanders efficiency gains by operating with a panel. This led to a new set of estimators known in literature as Common Correlated Effect (CCE), which essentially consists of increasing the model to be estimated by adding the averages of the individuals in each time t, of both the dependent variable and the specific regressors of each individual. Finally, two Stata codes developed for the evaluation and treatment of the cross-section dependence are presented.
Keywords: 330